2007
DOI: 10.3758/bf03193598
|View full text |Cite
|
Sign up to set email alerts
|

The effects of divided attention on auditory priming

Abstract: The concept of attention plays a central role in theories of memory, a view supported by a long history of findings that attentional state during encoding affects later memory performance (e.g., Broadbent, 1958;Cowan, 1995;Norman, 1969). Traditional research on this topic has focused on explicit memory. More recently, researchers have addressed the relationship between attention and implicit memory, spurred by the well-documented dissociations between implicit and explicit memory (Mulligan, 2003b;Roediger & Mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 69 publications
2
24
0
Order By: Relevance
“…For example, the MBE magnitude is unaffected by encoding depth, extended duration of fragment presentation, or inclusion of very specific instructions to avoid the influence of blocking words (Landau and Leynes, 2006;Leynes et al, 2008;Logan and Balota, 2003;Smith and Tindell, 1997). Kinoshita and Towgood (2001) argued that explicit memory mechanisms underlie blocking because dividing attention at study reduced MBE magnitude; however, this result is not clear evidence against the working hypothesis that implicit memory contributes to the MBE because divided attention can impair both explicit and implicit task performance (Mulligan et al, 2007). Consequently, additional evidence regarding blocking mechanisms is needed to fully resolve this issue.…”
Section: Introductionmentioning
confidence: 90%
“…For example, the MBE magnitude is unaffected by encoding depth, extended duration of fragment presentation, or inclusion of very specific instructions to avoid the influence of blocking words (Landau and Leynes, 2006;Leynes et al, 2008;Logan and Balota, 2003;Smith and Tindell, 1997). Kinoshita and Towgood (2001) argued that explicit memory mechanisms underlie blocking because dividing attention at study reduced MBE magnitude; however, this result is not clear evidence against the working hypothesis that implicit memory contributes to the MBE because divided attention can impair both explicit and implicit task performance (Mulligan et al, 2007). Consequently, additional evidence regarding blocking mechanisms is needed to fully resolve this issue.…”
Section: Introductionmentioning
confidence: 90%
“…Similar results were obtained by Mulligan (2002Mulligan ( , 2003; see also Mulligan & Hornstein, 2000) with the perceptual identification task. Convergent results in the auditory modality were achieved by Mulligan, Duke, and Cooper (2007): They showed that a distractor task with high response frequency disrupted priming on the auditory versions of perceptual identification, word-stem, and word-fragment completion tasks. Finally, Mulligan and Peterson (2008) demonstrated that even the lexical decision (which had previously showed a strong resilience to attentional manipulations; Szymanski & MacLeod, 1996) was impaired by a modified version of the Stroop task, in which the attention was manipulated across distinct objects rather than within the same words (e.g., participants were requested to do colour judgements about Xs flanking the words).…”
Section: Divided Attentionmentioning
confidence: 96%
“…We also used distracting tasks that required frequent rather than occasional responding and paid careful attention to the timing of distracting and implicit memory test stimuli. Response frequency and timing of tasks are both factors that are known to modulate DA effects on priming in some implicit memory tasks ( Mulligan, 2003 ; Mulligan et al, 2007 ). Despite those design features, there was no hint of a DA effect across two experiments, at least when the full samples in both experiments were considered.…”
Section: Discussionmentioning
confidence: 99%
“…1 Lozito and Mulligan (2010) used a variety of distracting tasks and multiple implicit memory tasks such as perceptual identification, word-stem completion, and category exemplar generation (CEG) to investigate retrieval-phase DA effects on implicit memory. Priming was unaffected in every case, regardless of whether distracting tasks required frequent or occasional responses (which can sometimes determine whether encoding-phase DA effects occur for implicit memory; see Mulligan, 2003 ; Mulligan et al, 2007 ), and regardless of whether distracting task materials overlapped with the implicit memory tasks. Together, these studies provide good support for the automaticity hypothesis, and they join additional studies that have reported little or no effect of retrieval-phase DA on other automatic uses of memory such as artificial grammar learning, false fame, or estimates of familiarity in recognition ( Jacoby et al, 1989 ; Jacoby, 1991 ; Helman and Berry, 2003 ).…”
Section: Introductionmentioning
confidence: 99%